Impact of Industrial Activities on Buduran River Water Quality in Sidoarjo Regency Using The STORET Method - Listin Fitrianah; Heni Lestari (Universitas Islam Raden Rahmat, Malang, 2026)
The Buduran River in Sidoarjo Regency is a water source used by the community for domestic, agricultural, and fishery purposes. Increasing industrial and residential activities along the river have raised concerns about water pollution, particularly by organic matter and heavy metals. This study aims to analyze the water quality status of the Buduran River based on physicochemical parameters using the STORET method. Water samples were taken from two locations with two repetitions, a total of 8 samples, and tested for temperature, pH, BOD, COD, and the heavy metal Pb. The results showed that temperature and pH were in accordance with the Class II quality standards of the Republic of Indonesia Government Regulation Number 22 of 2021. The levels of BOD, COD, and the heavy metal Pb exceeded the established threshold. The BOD parameter at location points 1 and 2, namely 12.3 mg/L and 20.1 mg/L, respectively, exceeded the quality standard limit of 3 mg/L. The COD parameter at the second location point exceeded the quality standard limit of 29 mg/L because it was above 25 mg/L. The Pb metal parameter at location 1 was 1.63 and the second location was 1.22 mg/L. Both exceeded the quality standard limit. This indicates that the river in Buduran is experiencing water pollution. The role of the government and industrial managers in managing rivers due to industrial activities in mentoring and implementing technology.The scoring calculation using the STORET method showed that the water quality status of the Buduran River in Sidoarjo was moderately polluted at all points, with a score of -12 at locations 1 and 2 and a score of -18. These findings indicate the need for better waste management to maintain the sustainability of the river ecosystem.